The usage of accounting database system / Alysha Anuar - Anuar, Alysha (Universiti Teknologi MARA, Sarawak, 2014)
Pustaka Negeri Sarawak was built as a major information resource centre and as the centre of information services for the public and private sectors. It links itself with libraries, archives and information centres elsewhere in Sarawak and throughout Malaysia. It also provides access into and from publicly accessible international information centres. Its complex serve as a community centre of knowledge and cultural enlightenment, where Malaysians in Sarawak can not only access a wide store of information, in the form of both printed and electronic media but also gather for educational and cultural exchanged, programmes and participate in many other activities conducted by the organisation. Pustaka Negeri Sarawak is a library, but not just any library. It is an investment for everyone’s future. The building and services are thoughtfully conceived and designed to enable anyone to use it. Practical things like a childcare centre. Distinctive things like the Special Needs room, things that are not that noticeable, like automatic doors and wheelchair-friendly aisles. Researchers can look up the Special Collections here, everything ever written about Borneo, both facts and fiction. It is a storehouse of knowledge, presented in the most technologically advanced way possible.